Kelor Leaves Infusion as a Alternative in Increasing the Volume of Breastmilk and Birth Weight in Newborn - Diah Evawanna Anuhgera; Nikmah Jalilah Ritonga; Riris Sitorus (Jurnal Kebidanan Kestra, 2022)
Background: An increase in the volume of breast milk and baby weight is the hope of every mother during breastfeeding. The consistency and quality of breastfeeding is determined by a mother. Moringa leaves, which is a typical plant in Indonesia, have many benefits, especially to increase milk production and nutrition for infants and children in the growth process. The purpose of this study was to determine the effect of morinaga leaves in increasing the volume of  breast milk and birth weigh of babies.